Asphalt to ecosystems : design ideas for schoolyard transformation - Danks, Sharon Gamson (New Village Press, 2010)
"Case studies from North America, Scandinavia, Great Britain, and Japan demonstrate natural outdoor learning and play environments that support hands-on interdisciplinary lessons and expand the possibilities for schoolyard recreation, while nurturing healthy imagination and socialization"--Provided by publisher